The Effects of Independent Non-Executive Directors (INED) on Company Performance – A Comparison of Family and Non- Family-Controlled Business - Li, Kevin Chi Keung; Ming, Agol Ho Wai (Journal of Applied Business and Economics, 2024)
This study will examine the influence of and relationship between independent non-executive directors (INEDs) and the performance of family -and non-family -controlled businesses listed on the Hong Kong Stock Exchange (SEHK). It is well known and reported that family-managed businesses dominate different industrial sectors around the world and that one third of the companies listed in the Standard and Poor 500 Index in the US are managed by families, who are also the companies’ major shareholders. Many previous studies argue that INEDs can improve corporate governance and firm performance. It is worthwhile to study whether the increase in the number of INEDs will affect the behaviour of major shareholders and the performance of these family-managed firms or not. The study aims to help policymakers/regulators determine whether further revision of the current INED policy is necessary. The results can be further investigated and applied to other emerging markets/regions worldwide with family-controlled enterprises.